2022
DOI: 10.3390/cells11223692
|View full text |Cite
|
Sign up to set email alerts
|

CAR-Macrophages and CAR-T Cells Synergistically Kill Tumor Cells In Vitro

Abstract: Chimeric antigen receptor (CAR)-expressing macrophages (CAR-M) have a great potential to improve cancer therapy, as shown from several recent preclinical studies. However, unlike CAR-T cell therapy, which has been widely studied, the efficacy and limitations of CAR-M cells remain to be established. To address this issue, in the present study, we compared three intracellular signaling domains (derived from common γ subunit of Fc receptors (FcRγ), multiple EGF-like-domains protein 10 (Megf10), and the CD19 cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“… Could be effective in multiple myeloma and other hematologic cancers with these antigen expressions. [ 132 ] …”
Section: Immune Cell Interaction With Tumorsmentioning
confidence: 99%
“… Could be effective in multiple myeloma and other hematologic cancers with these antigen expressions. [ 132 ] …”
Section: Immune Cell Interaction With Tumorsmentioning
confidence: 99%
“…The innate ability of CAR macrophages to boost the function of endogenous T cells suggests they could enhance CAR T cell activity. When co-cultured in vitro , CAR macrophages and CAR T cells exhibited remarkable synergy in cytotoxic activity against tumor cells ( 186 ). While CAR macrophages support the function of CAR T cells by upregulating costimulatory ligands (CD86 and CD80), CAR T cells also secrete proinflammatory cytokines that drive CAR macrophages towards an M1 polarization.…”
Section: Car Cells Generated From Innate Immune Cellsmentioning
confidence: 99%
“…Liu et al compared three common engulfment receptor intracellular domains (FcRγ, Megf10, and PI3K recruitment domain of CD19) in CAR-M for their phagocytosis and killing ability. CAR-M FcRγ showed the most potent phagocytic and killing capacity among the three CAR-Ms [ 202 ]. They also found that CAR-M and CAR-T have a synergistic effect against tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effect of CAR-M and CAR-T against tumor cells probably depends on a feedback loop triggered by the activation of CAR-T. The inflammatory factors secreted by CAR-T augment the cytotoxicity of CAR-M by inducing macrophage M1 polarization and increasing the expression of costimulatory ligands on CAR-M, which may promote the fitness and activation of CAR-T cells in turn [ 202 ]. Klichinsky et al also demonstrated that CAR-Ms constructed with either the CD3ζ or FcRγ activating domain are functionally similar in phagocytosis assays [ 198 ].They generated CAR macrophages (CAR-Ms) by transducing the monocyte-derived pro-inflammatory macrophages with adenoviral vectors encoding anti-HER2 CAR.…”
Section: Introductionmentioning
confidence: 99%